2020
DOI: 10.3390/su12114544
|View full text |Cite
|
Sign up to set email alerts
|

Icebergs of Expertise-Based Leadership: The Role of Expert Leaders in Public Administration

Abstract: There is a pressing need for public administration leaders to exhibit expertise-based intuitive leadership traits for developing countries to respond to sustainability challenges. While the importance of explicit and tacit knowledge to underpin expertise-based intuitive decision-making is known, public service leaders of developing countries can lack these traits. It is necessary to explore the reasons for leadership skills gaps in order to define remedial actions, such as better executive development training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…These resources can be tangible or immaterial organizational assets and human capital that allow organizations to enact new value-creation strategies [39]. However, not all organizations and systems are inclined to resource creation and expansion for a variety of reasons, like their inability to anticipate how external changes will affect their effectiveness [40], preference to maintain existing routines [41], fear of changing status [42] and losing their ability to reliably produce and offer their products or services [43], and the lack of knowledge or expertise in building a new resource base [44].…”
Section: Agricultural Knowledge and Innovation Systems In A Digitaliz...mentioning
confidence: 99%
“…These resources can be tangible or immaterial organizational assets and human capital that allow organizations to enact new value-creation strategies [39]. However, not all organizations and systems are inclined to resource creation and expansion for a variety of reasons, like their inability to anticipate how external changes will affect their effectiveness [40], preference to maintain existing routines [41], fear of changing status [42] and losing their ability to reliably produce and offer their products or services [43], and the lack of knowledge or expertise in building a new resource base [44].…”
Section: Agricultural Knowledge and Innovation Systems In A Digitaliz...mentioning
confidence: 99%
“…High academic performance (i.e., knowledge skills) combined with extracurricular activities (that help develop social skills and personal qualities) increase the perceived employability of business graduates in the industry [25]. Hanif et al [26] have identified a strong need for effective training on behavioral and interpersonal skills for project directors and managers. Dubey and Tiwari [27] note a sizable gap in the soft skills possessed by the graduates and those required by the industry.…”
Section: Project Management Personal Competencesmentioning
confidence: 99%
“…It is important to note that a significant number of these skills are directly related to the capacity of the project manager to impact those on their team [56]. Hanif et al [26] write that a deficit in formal training leads to knowledge gaps that undermine effective decision-making. Using Revised BT, LOs were constructed for these specific concepts on the three cognitive levels of the BT, as shown in Table 4.…”
Section: Training Design Using Bloom's Taxonomymentioning
confidence: 99%
“…Intuitive knowing accessed in this way can contribute greatly to high level performance (Kandasamy et al 2016). Hanif et al (2020) investigated the utility of expert intuition within public sector leaders in a developing country, Pakistan. They commented on the relevance of such intuition for sustainable development.…”
Section: Explorations Of the Nature Of Intuition In Psychologymentioning
confidence: 99%